Autoeficácia ocupacional e regulação dos estados emocionais de residentes da área da saúde no contexto da pandemia do Covid-19 no Brasil - Da Cas, Andressa Rocha (2022)
Health professionals are a vulnerable population to psychological distress. Two significant characteristics in the work of these professionals are the heavy workload and the continuous patient care activities. In addition, the COVID-19 pandemic has changed the routine of hospitals, from basic hygiene practices to the management of patients with a new disease, enhancing psychological impacts during this period. The objective of the present study was to investigate occupational self-efficacy and emotional regulation difficulties in health professionals in training, as well as psychological symptoms during the pandemic period. Analyzes were performed on two cross-sectional studies. The first study is an article which sought to analyze occupational self-efficacy through the Occupational Self-Efficacy Scale - Brief Version (OSS-SF), symptoms of depression, anxiety and stress through the Depression, Anxiety and Stress Scale (DASS-21) and the relationship between these constructs. The second study is an article which evaluated the relationship between psychological symptoms, occupational self-efficacy and emotional regulation difficulties using the Difficulties in Emotional Regulation Scale (DERS).